2018
DOI: 10.1038/s41598-018-33450-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long-term daylight deprivation on retinal light sensitivity, circadian rhythms and sleep during the Antarctic winter

Abstract: Long-term daylight deprivation such as during the Antarctic winter has been shown to lead to delayed sleep timing and sleep fragmentation. We aimed at testing whether retinal sensitivity, sleep and circadian rest-activity will change during long-term daylight deprivation on two Antarctic bases (Concordia and Halley VI) in a total of 25 healthy crew members (mean age: 34 ± 11y; 7f). The pupil responses to different light stimuli were used to assess retinal sensitivity changes. Rest-activity cycles were continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
2
30
0
1
Order By: Relevance
“…The paper also concluded that hypoxia has a significant effect on sleep, likely due to periodic breathing. Kawasaki et al (2018) studied the effect of long-term daylight deprivation on retinal sensitivity, sleep and circadian rest-activity.…”
Section: Sleepmentioning
confidence: 99%
“…The paper also concluded that hypoxia has a significant effect on sleep, likely due to periodic breathing. Kawasaki et al (2018) studied the effect of long-term daylight deprivation on retinal sensitivity, sleep and circadian rest-activity.…”
Section: Sleepmentioning
confidence: 99%
“…Delay in sleep timing, and an increase in sleep fragmentation, were also found in winter by Francis et al (2008). Winter delay for bed-, wake-, sleep start-, and sleep end-time were also observed by Kawasaki et al (2018). In their study, two Antarctic stations, Halley and Concordia, were investigated, aiming at highlighting possible differences between the two altitudes.…”
Section: Polar Environmentsmentioning
confidence: 99%
“…The daylight-like lighting is also beneficial to visual comfort, alertness, mood, and sleep quality [17], [22], [23]. Many researchers pursued mimicking dynamic daylight by the novel lighting of LEDs and OLEDs [6]- [12], [15], [17]- [19], [24]- [26]. However, a dynamic and full visible spectrum of daylight is hardly obtained by mixing monochromatic and/or phosphor-coated LEDs because of the width, the shape of the LED spectra, the green gap and the computation capability [6], [12], [17], [27].…”
Section: Introductionmentioning
confidence: 99%